Implikasi Keterlibatan Pejabat Pembuat Akta Tanah Menghitung Pajak Penjual dan Pajak Pembeli dalam Transaksi Jual Beli Tanah - Hafizh Windarrazan; Budi Ispriyarso (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This study aims to analyze the implications of the involvement of Land Deed Officials (PPAT) in assisting the calculation of seller and buyer taxes in land sale and purchase transactions. The research employs a normative legal method using statutory and conceptual approaches. The results indicate that PPAT is not authorized to determine the amount of tax but functions as a public official responsible for ensuring the fulfillment of administrative requirements, including tax obligations prior to the signing of the deed. In practice, PPAT’s involvement in estimating Final Income Tax and Duty on the Acquisition of Land and Building Rights helps parties plan transaction costs and improve efficiency. However, validation mechanisms by tax authorities may result in differences between estimated and actual tax amounts, potentially causing legal uncertainty and misunderstandings. Therefore, it is necessary to clarify the limits of PPAT’s role and apply prudential principles by providing disclaimers that calculations are only preliminary estimates. This is essential to maintain professional integrity and protect the interests of parties involved.